Exploring the role of online discussion forums in endorsing Egyptian undergraduates’ EFL learning - Morsi, Wesam Khairy; Elseoud, Mohamed Samir Abou (Edelweiss Applied Science and Technology, 2024)
eLearning Management systems (eLMS) are software applications used in universities worldwide to implement specific educational goals. eLearning platforms have several features that support traditional Face to Face (FTF) teaching and provide valuable opportunities for independent, self-paced learning. One of these features is the Online Discussion Forums (ODFs). This research paper investigates the role of ODFs in endorsing English as a Foreign Language (EFL) learning by examining students’ perceptions of its accessibility, peer/instructor interaction, assessment criteria, and discussion topics. The paper also investigates the influence of gender on students’ perceptions of the role of ODFs. This is a non-experimental research design, and 108 Egyptian undergraduates completed a semi-structured questionnaire of five dimensions. Percentages of frequency were calculated and quantitatively analysed via the SPSS. Research findings revealed male and female students’ positive perceptions of using ODFs in their learning process. Results also revealed that students highly perceived choice of topics and assessment as crucial factors for successful learning via ODFs, followed by peer/instructor interaction and accessibility of the tool. Implications for further research include employing ODFs to improve project-based teaching in different disciplines.